Islamic Education Management in the Perspective of the Qur'an - M. Munif (CV. Agrapana Media, 2026)
strategic planning, a lack of organizational order, and suboptimal supervision and evaluation systems. These conditions indicate a gap between the ideal Islamic values and managerial practices in Islamic educational institutions. In addition, studies on Islamic education management that are directly based on the Qur’an remain limited and tend to be normative in nature. Therefore, this study aims to analyze the principles of Islamic education management from the perspective of the Qur’an and to relate them to contemporary theories of Islamic education management. This research employs a qualitative approach using library research. The primary data consist of Qur’anic verses relevant to educational management principles, namely Qur’an Surah Al-Hasyr verse 18, Surah Ash-Shaff verse 4, and Surah Al-Mujadilah verse 7, while secondary data are obtained from scholarly literature and the works of Islamic education management scholars. Data were collected through documentation studies and analyzed using thematic analysis. The results indicate that the Qur’an contains principles of visionary and responsible planning, orderly and collective organization, as well as supervision and evaluation based on spiritual awareness. These principles are aligned with Azyumardi Azra’s theory of Islamic education management, which emphasizes professionalism and institutional modernization. The implications of this study suggest that the application of Qur’anic management principles can serve as a conceptual foundation for realizing effective, accountable, and sustainable management of Islamic educational institutions.